Multi-Element Exposure and Health Risks of Grains from Ambagarh Chowki, Chhattisgarh, India - Bhagyashri Wakhle; Saroj Sharma; Khageshwar Singh Patel; Piyush Kant Pandey; Antonela Blažević; Željka Fiket; Sema Yurdakul; Simge Varol; Pablo Martín-Ramos; Hanan M. Al-Yousef; Ramzi A. Mothana (Toxics)
Rice, wheat, and maize grains are staple foods, widely consumed for their mineral and nutritional values. However, they can accumulate toxic elements from contaminated soils, posing health risks. This study investigates the bioaccumulation patterns of 52 elements (including nutrients, heavy metals, and rare earth elements) in various parts (grain, husk, straw, and root) of cereals grown in a heavily polluted region. The results revealed that rice grains exhibited a higher accumulation (Σ33.4 mg/kg) of toxic elements (As, Cu, Cr, Ni, and Pb) than wheat (Σ26.6 mg/kg) and maize (Σ16.2 mg/kg) grains, with the high-yield RI64 cultivar (Σ47.0 mg/kg) being the most susceptible. Across the rice plant, accumulation increased in the order of grain < husk < straw < root. Elements like P, K, Cu, and Zn showed the highest enrichment. Worryingly, the most toxic elements, such as As, Pb, and Cd, exceeded permissible limits across grains, straws, and husks. Health risk assessment indicated that wheat and maize pose greater non-cancer and cancer risks than rice. Despite being grown in a highly contaminated region, the study identifies some rice cultivars like Luchai and Sarna as relatively safer options due to a lower accumulation of toxic elements.